Outsourcing in The Digital Sector and The Protection of Workers’ Rights - Muhammad, Fadil; Nurrachman, Alfan Dzikria; Sofian, Muhamad (Indonesia Law Reform Journal, 2026)
The advancement of digital technology has given rise to the gig economy, which is increasingly dominating the global labor market. A key aspect of this development is digital outsourcing, which offers inclusive opportunities for workers in developing countries, while simultaneously presenting significant challenges to the protection of workers' rights. This study seeks to examine the implications of digital outsourcing policies on worker protection within the context of labor law in Indonesia, highlighting both the positive and negative impacts, the increasing trends observed in Indonesia, and the associated regulatory challenges. The research employs a normative legal analysis, drawing on a statutory regulatory approach, complemented by a literature review of relevant prior studies. The findings reveal that digital outsourcing has positive effects, including expanded global job access, enhanced flexibility, and potential income growth. However, it also has negative consequences, such as legal status ambiguity, inadequate social protection, and excessive working hours. In Indonesia, outsourcing practices are grounded in Manpower Law and the Job Creation Law; however, regulations specifically addressing digital workers remain insufficiently comprehensive. Consequently, labor laws must be reinforced with targeted provisions responsive to digital work models, particularly with regard to the integration of personal data protection laws and cyber law. This research contributes to the ongoing discourse on the need to harmonize labor law with the evolving landscape of digitalization, ensuring equitable protection for workers engaged in digital outsourcing.